Adaptation of the Global Perceived Stress Scale in college peruvian students - Guzmán-Yacaman, Jaime Enrique (2018)
The present study aims to validate the Global Perceived Stress Scale on a Peruvian college students sample, involving young scholars of a state-funded program. The adaptation process involved a double translation from the original version, a linguistic comparison using the scales adapted in Chile and Mexico, and judgement criteria, as well as a pilot test. Participants were 332 college scholarship students. Results with the Confirmed Factorial Analysis confirmed the bifactorial model of the EPGE-13. Moreover, convergent and divergent validity was done with the SPANAS test. Likewise, the scale demonstrate adequate reliability (internal consistency, ? = .79 for the factor of eustress and ? = .77 for the factor of distress). Demographic results indicated that there was more perceived stress in women than in men. There were no significant differences in stress according to birthplace.